The Parent Perception Toward Studying-at-Home Activity During Pandemic Covid-19: Persepsi Orang Tua Terhadap Kegiatan Belajar di Rumah Selama Pandemi Covid-19 - Ressa Dwi Citra PermataSari Triastono; Wahyu Taufiq (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to identify parents' perception of learning from home during the Covid-19 pandemic. This research is a qualitative descriptive research. In this study, respondents as many as 5 people consisting of parents who were given the initials P1, P2, P3, P4, P5. Data collection using qualitative case study method and data retrieval process in this study comes from interviews obtained by parents' perception of learning from home during the Covid-19 pandemic. Data analysis techniques in this research use descriptive qualitative analysis. The results of this study show that there is a perception of parents towards learning from home during the Covid-19 pandemic is considered less than optimal because the learning process is not directly carried out with teachers, the learning process must have technological tools in the form of gadgets in order to follow distance learning. In addition, the use of online learning parents have to buy additional quota even though there is free internet quota, but the use of free internet quota is used all the time for learning activities at less savings. Learning at home is done considering the health aspect becomes a very vulnerable aspect to this disaster because the ease of transmission from covid-19 is very fast and can infect anyone who makes contact with people with covid-19, especially for those who have a low immune system.